Inculturation of Tahlilan Tradition in Lampung and Banten - Mukri, Moh.; Hermanto, Agus (KALAM, 2021)
As a religious tradition, Tahlilan cannot be put in  isolation of debate among Indonesian Muslim society. In one side, it is believed as part of Islamic teachings which do not contradict with the Shari’a, while the other considers it as a syncretistic practice that has no guidance in the Qur’an and As-Sunnah.  Apart from the controversy surrounding it, this study aims to examine, both philosophically and sociologically, how the actual process of inculturation between religious and cultural values in the Tahlilan tradition is constructed and embedded, so that it persists as a tradition constantly alive. As the field research, this study explores data from two different areas, namely Lampung and Banten. As a result, this study would like to describe although the Tahlilan tradition in both areas has the same essence and purpose, as al-adah muhakamahor customs, to recite the holy verses of the Qur’an, dzikir, and pray to the spirit of someone who has died in order to gain God’s forgiveness, the inculturation of both areas has its own distinctions and peculiarities.